Performance Evaluation of Spectrum Sensing Using Recovered Secondary Frames With Decoding Errors - Tang, Liang; Chen, Yunfei; Nallanathan, Arumugam; Hines, Evor L. (IEEE transactions on wireless communications, 2012)
The performance of spectrum sensing using the recovered secondary frames is analyzed. Unlike the previous work that assumes perfect decoding of the secondary signal, the new analysis takes the decoding errors into account and therefore provides a more realistic comparison between the new model and the conventional model. Both the receiver operating characteristics curves for spectrum sensing and the achievable throughput for data transmission are derived. Effects of fading and error control codes are also investigated. Numerical results show that the new model that considers the decoding error outperforms the conventional model when the number of transmitted secondary frames is below a certain threshold. An upper bound performance can also be obtained by ignoring the decoding error. The threshold is determined by the primary user traffic, the spectrum sensing technique and the secondary signal modulation scheme.